2015
DOI: 10.1007/s00429-015-1003-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential frequency-dependent antidromic resonance of the Schaffer collaterals and mossy fibers

Abstract: To better understand information transfer along the hippocampal pathways and its plasticity, here we studied the antidromic responses of the dentate gyrus (DG) and CA3 to activation of the mossy fibers and Schaffer collaterals, respectively, in hippocampal slices from naïve and epileptic rats. We applied trains of 600 electrical stimuli at functionally meaningful frequencies (θ, β/γ and γ). The responses of the DG to θ frequency trains underwent rapid potentiation that lasted about 400 stimuli, after which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Interestingly, contrary to what has been found in the DG of animal models of epilepsy (for a review see Jefferys et al, 2012), fast ripples did not appear in the DG but in CA3. This suggests that the low amplitude fast ripples observed in the DG in this study, could be originated in CA3 and transmitted to the DG by CA3-hilar-DG projections or antidromically by the mossy fibers (Vivar et al, 2012;Franco et al, 2015).…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, contrary to what has been found in the DG of animal models of epilepsy (for a review see Jefferys et al, 2012), fast ripples did not appear in the DG but in CA3. This suggests that the low amplitude fast ripples observed in the DG in this study, could be originated in CA3 and transmitted to the DG by CA3-hilar-DG projections or antidromically by the mossy fibers (Vivar et al, 2012;Franco et al, 2015).…”
Section: Discussionmentioning
confidence: 59%
“…This field response had a characteristic negative component (Fig. 1b), representing multiple synchronous antidromic action potentials (Franco et al 2015). The following positive component ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…b), representing multiple synchronous antidromic action potentials (Franco et al . ). The following positive component (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, they showed that these receptors coexist with glutamate receptors in the post-synaptic site. GABA acting on GABA A receptors modulates the excitability of the MFs (Ruiz et al, 2003;Treviñ o and Gutié rrez, 2005;Franco et al, 2015) and therefore further release of neurotransmitter (Treviñ o and Gutié rrez, 2005;Yamamoto et al, 2011). On the other hand, it is well known that GABA B receptors are present in the MF terminals and their activation with the agonist baclophen inhibits the release of GABA from the MFs (Gutié rrez, 2002).…”
Section: The Neurotransmitter Phenotype Of the Granule Cells Is Plasticmentioning
confidence: 99%
“…Granule cells from control rats express VGlut but not VGAT, while GCs from epileptic rats (C 2 ) express both VGlut and VGAT mRNAs. the MFs acts to regulate further release of neurotransmitter and modulates information transfer of the MFs by acting on GABA A (Ruiz et al, 2003;Treviñ o and Gutié rrez, 2005;Franco et al, 2015;Yamamoto et al, 2011), as well as on GABA B receptors (Gutié rrez, 2002;Safiulina and Cherubini, 2009;Cabezas et al, 2012;Valente et al, 2015).…”
Section: The Neurotransmitter Phenotype Of the Granule Cells Is Plasticmentioning
confidence: 99%